Searching for the most profitable and sustainable investment strategy: evidence from sovereign bond funds - Vargas, Maria; Vicente, Ruth; Muñoz, Fernando (Journal of Business Economics and Management, 2014)
The aim of this study is to provide the sovereign bond fund investor with a guide to finding the most profitable and sustainable investment strategy. For this purpose, a Global Sustainable Competitiveness Index is applied to a sample of 48 funds. We have conducted a best-in-class analysis, and our evidence supports the idea that the best strategy consists of investing in funds representing high GDP-per-capita countries, and registering the best-in-class sustainable performance scores. Additionally, other useful findings are that the screening of the funds is beneficial with respect to sustainable performance, and that there is no strong relationship between sustainability and GDP per capita.